Hormone-disruptive chemical contaminants in food - Pongratz, Ingemar; Bergander, Linda Vikström (Issues in toxicology ;, 2012)
Today, we are surrounded by a multitude of different chemicals that are essential components of our everyday life. As a consequence, there are various hazardous substances like dioxins, phthalates and flame-retardants circulating in the environment. These have an impact on ecosystems, wildlife and possibly human health. In recent years, the phenomenon called endocrine disruption has raised considerable concern. This book discusses the scientific basis of this issue using epidemiological and experimental in vitro and in vivo data about chemicals targeting the hormonal systems. It also provides.